FRI0091 Australian economic evaluation of tocilizumab monotherapy vs adalimumab monotherapy in patients with rheumatoid arthritis based on the adacta trial. (23rd January 2014) - Ngo, P.; Sorathia, R.; Todd, C.; Jones, G.; Nash, P.
Abstract : Background: The ADACTA trial 1 showed that tocilizumab (TCZ) monotherapy was superior to adalimumab (ADA) monotherapy in reducing signs and symptoms in adult patients with ≥ 6-month duration of rheumatoid arthritis (RA) who were either intolerant to methotrexate (MTX) or for whom continued MTX treatment was inappropriate. Randomised patients received TCZ 8 mg/kg IV monotherapy every 4 weeks (plus placebo ADA) or ADA 40 mg monotherapy subcutaneously (SC) every other week (plus placebo TCZ) for 24 weeks. Objectives: To perform, from an Australian health care perspective, an economic evaluation of total treatment and incremental costs per responder of monotherapy, TCZ versus ADA over a 24 week period in MTX intolerant/contraindicated RA patients based on the ADACTA trial. Methods: Total treatment costs were calculated based on the Schedule of Pharmaceutical Benefits, mean TCZ weight-76.06kg (reported in ADACTA) and dosages reimbursed in Australia. Calculations assumed no vial sharing; therefore total treatment costs for TCZ are equivalent for patients 76.0kg-80.0kg which may be more appropriate to Australian patients. Estimates for medical resource use costs (drug administration; MBS item-13915, specialist consultation; MBS item-116) were obtained from the Schedule of Medicare Benefits. The base-case analysis assumed 59% and 41% of patients would be treated in private and public settings, respectively, based on TCZ RA script-processing by Medicare Australia in 2012. Incremental costs per responder were determined based on net differences in TCZ and ADA total treatment costs, ACR response and DAS28 remission rates from ADACTA. Sensitivity analyses were conducted by modifying the highest uncertainty parameters (proportion of public/private use and patient bodyweight). Results: TCZ monotherapy results in lower total treatment costs (in Australian dollars) per patient over 24-weeks compared to ADA monotherapy (Table ; TCZ-9, 739; ADA-10, 722). Furthermore, cost per responder for all efficacy outcomes is lower with TCZ than ADA (DAS28 remission-24, 408 per TCZ responder; 102, 117 per ADA responder and ACR 20/50/70-14, 983/20, 633/29, 966 per TCZ responder; 21, 705/38, 569/59, 901 per ADA responder). TCZ use is associated with incremental cost savings of 3, 344 per patient achieving DAS28 remission and 6, 303/5, 068/6, 735 per ACR 20/50/70 responder. Conclusions: In RA patients where MTX is inappropriate, TCZ monotherapy may lead to significant cost savings over 6-months of therapy when compared to ADA monotherapy, based on response rates extrapolated from ADACTA to the Australian setting. References: Gabay C, et al. Ann Rheum Dis 2012;71(Suppl3):152 Acknowledgements: The ADACTA study was sponsored by F. Hoffmann-La-Roche Ltd. Disclosure of Interest: P. Ngo Employee of: Roche Products Pty Limited (Australia), R. Sorathia Employee of: Roche Products Pty Limited (Australia), C. Todd Employee of: Roche Products Pty Limited (Australia), G. Jones: None Declared, P. Nash: None Declared